PREVENTIVE BEHAVIOR AMONG MEDICAL STUDENTS DURING THE COVID- 19 PANDEMIC - Đokić, Ivana; Đokić, Milena; Đokić, Ana; Milin Lazović, Jelena (Medicinski podmladak, 2023)
Introduction: The corona virus has shown that it does not have a seasonal character, that it spreads very easily from one person to another, if prevention measures are not applied. In addition to vaccination, which is undoubtedly the most important measure to prevent COVID- 19 infection, responsible behavior (wearing masks, hand hygiene, respecting physical distance), especially in this period of increasing the number of patients and the emergence of new strains, is also an important measure of disease prevention and control. The aim of this study is to examine the preventive behavior of medical students during the COVID-19 pandemic. Material and methods: The research was conducted in January 2021 as a cross-sectional study involving 373 students of the Medical Faculty of the University of Belgrade. An electronic questionnaire was used to collect the data, which was created using Google Forms applications, and the completion of the questionnaire was voluntary and anonymous. The questionnaire consisted of 3 parts: sociodemographic characteristics and preventive behavior of medical students related to the COVID-19 pandemic. Results: About 80% of students often wore a protective mask and avoided touching their face, almost all often washed their hands, and about 90% rarely and occasionally wore gloves. The students washed and disinfected their hands significantly more often, avoided touching their faces with their hands, and covered their mouths and noses more often when sneezing and coughing. Also, female students were statistically significantly more likely to stay at home and disinfect items compared to male students. Conclusion: Knowledge of risky and preventive behavior related to COVID-19 as well as an adequate level of knowledge among students, positive attitudes and preventive behavior are key to ensuring effective prevention and control of the pandemic. Key words: prevention, behavior, medical students, COVID-19, pandemic